Pocket emergency medicine - Agrawal, Pooja; Zane, Richard D.; Kosowsky, Joshua M. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
Contains the essential information that residents and medical students in the emergency department need to have at their fingertips. This book includes major sections that cover symptoms and diseases of each organ system as well as infectious diseases, environmental exposures, hematology and oncology, pediatric emergencies, and toxicology.